Improving the age reading of East Greenland Atlantic cod (Gadus morhua) by determining otolith growth zone timing and annuli widths. (2nd September 2020) - Lyngby, Mette Svantemann; Rigét, Frank; Retzel, Anja; Hedeholm, Rasmus; Grønkjær, Peter
Abstract: Accurate and consistent age readings are cornerstones of age‐based assessment and management of exploited fish stocks. Otoliths are the preferred structure for age determination, often performed by counting the number of completed 001 zones. Uncertainty regarding the identification of the first translucent zone and the timing of translucent zone formation can cause skewed age determination even in species with otherwise clearly defined annuli. This study addresses an inter‐institutional discrepancy in age readings of the East Greenland Atlantic cod Gadus morhua L. By analysing the opacity of the otolith margin of cod sampled monthly from February to December, it was shown that translucent zones are formed primarily during March–May. Size distributions of the dorsal–ventral and proximal–distal widths of the first three translucent zones are provided as guide to their identification. This study provides new knowledge that resolves the discrepancy in age reading of East Greenland Atlantic cod.